Analisis Performansi Rantai Pasok Bawang Goreng Pada Industri Rumahan Azka Kabupaten Probolinggo - Amanda, Boyke Putra; Amir, Nur Ocvanny (Universitas Galuh, 2025)
Shallots are the largest agricultural production in Probolinggo Regency. Azka Home Industry processes red onions into fried onions to develop its business. However, there are several problems such as unstable prices and unstable supply of shallots. The objectives of this research are 1) to determine the product flow, money flow, and information flow in the fried onion supply chain flow at the Azka Home Industry. 2) to analyze the performance of the fried onion supply chain at the Azka Home Industry. Sampling used the